1976
DOI: 10.1002/pssa.2210370144
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological interpretation of heat flux volume rectification in Non-homogeneous media

Abstract: Investigations of the thermal conductivity of a non-homogeneous monocrystallineGaAs sample (1) revealed the presence of heat flux flow asymmetry with regard to the change of direction of the externally applied temperature difference. Experiments on four individual parts of the sample enabled to confirm that it wa8 really nonhomogeneous in the sense of thermal conductivity and manifested a dependence of the thermal conductivity coefficient (TCC) on temperature.Considering the above experimental facts, we write … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…As a result, the application of thermal diodes is limited to 'niche' applications such as heat distribution in spacecra. Since the observation of thermal rectication by Starr 10 several groups have realized thermal diodes based on different mechanisms: evaporation/ condensation, 11 infrared emission, 2 the difference in thermal coefficient at the junctions between two materials, 12 thermal potential barrier and strain at two material contacts, and the phonon anharmonicity in 1D lattices 7 (see also reviews 8,9,11 and therein references). Recently, a bulk thermal diode using two different cobalt oxides was reported by Kobayashi et al, 13 and nanostructured and two-dimensional materials are also being sought for more efficient thermal rectication.…”
mentioning
confidence: 99%
“…As a result, the application of thermal diodes is limited to 'niche' applications such as heat distribution in spacecra. Since the observation of thermal rectication by Starr 10 several groups have realized thermal diodes based on different mechanisms: evaporation/ condensation, 11 infrared emission, 2 the difference in thermal coefficient at the junctions between two materials, 12 thermal potential barrier and strain at two material contacts, and the phonon anharmonicity in 1D lattices 7 (see also reviews 8,9,11 and therein references). Recently, a bulk thermal diode using two different cobalt oxides was reported by Kobayashi et al, 13 and nanostructured and two-dimensional materials are also being sought for more efficient thermal rectication.…”
mentioning
confidence: 99%
“…This mechanism was initially proposed by Marucha et al when they performed experiments on inhomogeneous GaAs and found a directional dependence of the thermal conductivity [28]. Marucha et al later analyzed the system using the one-dimensional Fourier equation and found that this temperature dependence of the thermal conductivity would result in thermal rectification [29]. The experimental and theoretical work by Marucha et al showed promise for thermally rectifying systems, but later work by Hudson in 1976 showed that their results may not entirely be a result of the effect of the thermal conductivity and may be enhanced by non-uniform isotherms over the cross-section of the specimen [22].…”
Section: Temperature Dependence Of Thermal Conductivity At Interfacesmentioning
confidence: 88%
“…The heat conduction of the contact surface formed by two different solid materials contacting each other can be direction-dependent (the heat transfers in one direction much faster than in the other), which is called the thermal rectification phenomenon. The thermal rectification can be realized in many different ways, such as different temperature-dependent thermal conductivities between two materials, [1][2][3][4][5][6][7][8] asymmetric electron transport, [9,10] interface thermal barrier, [11][12][13] roughness, and flatness in surface contact, [14][15][16] strain warping between two solids, [17][18][19][20][21][22][23] asymmetry of nanostructures, [4,24,25] non-uniform mass, [26][27][28] anharmonic/nonlinear lattices, [29][30][31][32][33][34][35][36] and composite metamaterials. [37] As early as in 1936, a solid state rectifier using copper oxide has been proposed.…”
Section: Introductionmentioning
confidence: 99%